From common lands (partitioning) to confraternity lands. The liberal confiscation of the Nahua of the south of Jalisco (1824-1856) - Monroy Merchán, María del Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article reconstructs the confiscation process of the communal property of the indigenous Nahua people from the south of Jalisco between 1824 and 1856. The objective is to reveal how the Nahuas made use of property by holding individual land titles. Based on the revision of the documental corpus of the lands of the south of Jalisco, it is identified how, during the first liberal period, the confiscation process wasdeveloped step by step in each of the communal spaces held by the Nahuas, from the fundo legal lands and the partitioned land to the confraternity lands. This process was developed in parallel with the consolidation of the municipalities, which were the principal promoters of private property. The deedsto the lands in the name of private subjects allowed them to become transferable goods, which in this way consolidated the hacienda scheme in the region of study.